Exogenous Biological Renal Support Improves Kidney Function in Mice With Rhabdomyolysis-Induced Acute Kidney Injury - Liu, Chao; Chi, Kun; Geng, Xiaodong; Hong, Quan; Mao, Zhi; Huang, Qi; Liu, Dong; Wang, Yiqin; Zhang, Ying; Zhou, Feihu; Cai, Guangyan; Chen, Xiangmei; et al. (Frontiers in Medicine, 2021)
Background Rhabdomyolysis (RM) is a clinical syndrome characterised by the breakdown of skeletal muscle fibres and release of their contents into the circulation. Myoglobin-induced acute kidney injury (AKI) is one of the most severe complications of RM. Based on our previous study, exogenous biological renal support alleviates renal ischaemia-reperfusion injury (IRI) in elderly mice. This study aimed to determine whether exogenous biological renal support promoted renal recovery from RM-induced AKI and to preliminarily explore the mechanisms involved. Methods A parabiosis animal model was established to investigate effects of exogenous biological renal support on RM-induced AKI. Male wild-type C57BL/6 mice and C57BL/6-TgN (ACTb-EGFP) transgenic mice were used to determine whether shared circulation was established among parabiotic pairs 3 weeks after parabiosis surgery. Mice were divided into three groups: the control group (sterile saline injected); RM group (glycerol (8 mL/kg) injected); and parabiosis + RM group (three weeks after the parabiosis model was established, the recipient mouse was injected with glycerol). Blood samples and kidney tissue were collected for further processing 48 hours after RM induction. Bioinformatics analysis was conducted with Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis, functional enrichment analysis and clustering analysis. Results At 48 hours after the procedure, all mice survived. Exogenous biological renal support attenuated the histological and functional deterioration in RM-induced AKI in mice. Bioinformatics analysis identified key pathways and proteins involved in this process. We further demonstrated that exogenous biological renal support ameliorated kidney injury through multiple pathways, including suppressing the complement system; attenuating oxidative stress, inflammation, and apoptosis; and increasing proliferation. Conclusions Exogenous biological renal support provided by parabiosis can improve renal function in RM-induced AKI by suppressing the complement system; decreasing oxidative stress, inflammation, and apoptosis; and promoting tubular cell proliferation. Our study provides new ideas for effectively preventing and treating RM-induced AKI and provides basic research evidence for the use of bioartificial kidneys to treat RM-induced AKI.